2021
DOI: 10.14330/cwr.2021.7.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Cases in China: Feilin v. Baidu and Tencent Shenzhen v. Shanghai Yingxin

Abstract: In 2019, two court rulings in China on the issue of copyrightability of AI creations received international attention. It was reported that in Feilin v. Baidu, known as the first AI case, the Beijing Internet Court denied copyright of AI creations, whereas the Shenzhen Nanshan District People's Court acknowledged copyright of AI creations in the Tencent Dreamwriter case. The two cases, however, were quite similar, as they acknowledged copyright of AIassisted, not AI-generated, written works and recognized thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…One of the cases is the Feilin v. Baidu, involves a ruling by the Beijing Internet Court in China regarding the copyright protection of an AI-generated work. The disputed work was a report titled "Analytical Report on the Judicial Big Data in the Film and Entertainment industry: Film Industry in Beijing", which was created using software called Wolters Kluwer China Law and Reference [14].…”
Section: Analysis Of Chinese Court Decisions Related To Ai Copyrightmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the cases is the Feilin v. Baidu, involves a ruling by the Beijing Internet Court in China regarding the copyright protection of an AI-generated work. The disputed work was a report titled "Analytical Report on the Judicial Big Data in the Film and Entertainment industry: Film Industry in Beijing", which was created using software called Wolters Kluwer China Law and Reference [14].…”
Section: Analysis Of Chinese Court Decisions Related To Ai Copyrightmentioning
confidence: 99%
“…Some drawings and words in the disputed report were not the same or similar to those in the software-generated report. The court concluded that the disputed report had not been generated by the software alone and was created by the plaintiff's team, making it eligible for copyright protection under Chinese law [14].…”
Section: Analysis Of Chinese Court Decisions Related To Ai Copyrightmentioning
confidence: 99%
See 2 more Smart Citations